Morphological variability of the fibularis brevis tendon in human fetuses - Olewnik, Łukasz; Zielinska, Nicol; Ruzik, Kacper; Podgórski, Michał; Kiciński, Przemysław; Diogo, Rui; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2024)
Introduction: The morphological variability of the fibularis brevis tendon in adults is well known. However, studies on its classification in the human fetus do not exist. The aim of this study was to provide the first comprehensive classification of the fibularis brevis tendon based on its insertion in human fetuses. The second aim of the study is to evaluate the prevalence of fibularis digiti quinti. Material and Methods: Forty-three spontaneously aborted human fetuses were studied (21 male, 22 female, 86 lower limbs). All were from a Central European population), aged 18–38 weeks of gestation at the time of death. Results: Three main types of fibularis brevis tendon were distinguished. The most common was Type I (77%), characterized by a single distal attachment. The tendon was attached to the tuberosity at the base of the fifth metatarsal, on the lateral side. The second most common was Type II (19%) - a bifurcated distal attachment. The main tendon was attached to the tuberosity at the base of the fifth metatarsal on the lateral side. Based on the attachment site of the accessory tendon, four subtypes were determined: Type IIA - the accessory tendon attached to the dorsal surface of the base of the fifth metatarsal. At the side of attachment, the fibularis brevis tendon was connected with a portion of the fibularis tertius tendon. Type IIB - the accessory tendon attached to the proximal part of the shaft of the fifth metatarsal. Type IIC - the accessory tendon was attached to the fascia covering the fourth interosseous space. Type IID - the accessory tendon was fused with fibularis longus tendon. Type III is the rarest (4%) - triple branched distal attachment. The main tendon was attached to the tuberosity at the base of the fifth metatarsal. The first accessory tendon was attached to the proximal part of the shaft of the fifth metatarsal, and the second accessory tendon was attached to the fascia covering the fourth interosseous space. The fibularis digiti quinti was present in 24 feet (28%) of the 86 lower limbs dissected. Conclusion: The fibularis brevis is characterized by high morphological variability. The proposed classification consists of three main Types (I-III), with Type II divided into subtypes (A-D). The fibularis digiti quinti is not closely related to the type of fibularis brevis tendon.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Anatomical variations; Fibularis brevis muscle; Fibularis brevis tendon; Foetuses